(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Objective: To find out association between impaired glucose tolerance and insulin resistance with Polycystic Ovary Syndrome (PCOS). Materials and methods: This cross-sectional comparative study was carried out on women with polycystic ovary syndrome (PCOS) admitted in the department of Obstetrics and Gynaecology, SSMC Mitford Hospital and BSMMU Dhaka over a period of 2 years from July 2008 to June 2010. Result: A total of 100 subjects, 50 cases and 50 controls were consecutively included in the study. The mean insulin resistance, impaired fasting glucose and impaired glucose 2 hours after 75 gm of glucose were observed to be significantly higher in cases than in controls (26.7+8.4 vs. 18.8+7.5 micro IU /ml, p<0.001) The prevalence of insulin resistance ,impaired fasting serum glucose and impaired glucose 2 hours after 75 gm of glucose also higher among study group compared to control group (70% vs. 12%;44% vs. 10% and 56% vs. 10 % respectively ). Conclusion: Impaired glucose tolerance and insulin resistance are useful parameter for diagnosis of PCOS. Bangladesh J Obstet Gynaecol, 2019; Vol. 34(2): 93-98